Goldenberry L.: phytochemicals and applications in human health - Ramos, Cynthia; Asmat , Percy; Lezama-Asencio , Pedro; Larco-León, Edinson; Chuna-Mogollón, Pablo; Hidalgo, Manuel (Revista Mexicana de Ciencias Agrícolas, 2025)
Goldenberry is a species of great socioeconomic importance in different countries of Latin America and Africa. At the phytochemical level, this species presents a variety of biologically important phytochemicals. Therefore, this paper aims to provide an exhaustive summary of Physalis peruviana goldenberry, focusing on its phytochemicals and applications in human health. This work was conducted in 2024; it indicates that, at the level of its fruits, there are terpenes, phenolic compounds, alcohols, steroids, withanolides, highlighting carotenoids and flavonoids, reduced levels of fat, high water content and vitamins A, B3, B6, C and E, as well as the minerals calcium, potassium, phosphorus and magnesium. This richness in phytochemicals and nutrients of goldenberry translates into significant health benefits thanks to its antioxidant, antibacterial and antiproliferative properties. In particular, goldenberry calyxes and leaf extracts have demonstrated antihepatotoxic, antifibrotic and antidiabetic activity. In summary, the goldenberry has an optimal nutritional content and it is necessary to optimize the bioavailability of its components to fully take advantage of its benefits. Due to its potential as a promising component in functional foods and phytomedicine, there is a need for more in-depth evaluations of its impact on the well-being of humanity.